Snowball Sampling: A Purposeful Method of Sampling in Qualitative Research - Fereshteh Ghaljaie; Mahin Naderifar; Hamideh Goli (Kerman University of Medical Sciences, 2017)
Background and Objectives Snowball sampling is applied when samples with the target characteristics are not easily accessible. This research describes snowball sampling as a purposeful method of data collection in qualitative research. Methods This paper is a descriptive review of previous research papers. Data were gathered using English keywords, including "review," "declaration," "snowball," and "chain referral," as well as Persian keywords that are equivalents of the following: "purposeful sampling," "snowball," "qualitative research," and "descriptive review." The databases included Google Scholar, Scopus, Irandoc, ProQuest, Science Direct, SID, MagIran, Medline, and Cochrane. The search was limited to Persian and English articles written between 2005 and 2013. Results The preliminary search yielded 433 articles from PubMed, 88 articles from Scopus, 1 article from SID, and 18 articles from MagIran. Among 125 articles, methodological and non-research articles were omitted. Finally, 11 relevant articles, which met the criteria, were selected for review. Conclusions Different methods of snowball sampling can be applied to facilitate scientific research, provide community-based data, and hold health educational programs. Snowball sampling can be effectively used to analyze vulnerable groups or individuals under special care. In fact, it allows researchers to access susceptible populations. Thus, it is suggested to consider snowball sampling strategies while working with the attendees of educational programs or samples of research studies.